A perturbation-based heuristic for the capacitated multisource weber problem - Zainuddin, Zaitul Marlizawati; Salhi, S. (Elsevier B.V., 2007)
This paper proposes a perturbation-based heuristic for the capacitated multisource Weber problem. This procedure is based on an effective use of borderline customers. Several implementations are considered and the two most appropriate are then computationally enhanced by using a reduced neighbourhood when solving the transportation problem. Computational results are presented using data sets from the literature, originally used for the uncapacitated case, with encouraging results